The association between SARC‐F status and quality of life in High Risk Foot Clinic patients. Issue 1 (1st January 2019) - Churilov, Irina; Churilov, Leonid; Proctor, Michelle; Galligan, Anna; Murphy, David; Westcott, Mark; MacIsaac, Richard J; Ekinci, Elif I
Abstract: Background: High Risk Foot Clinic (HRFC) patients have foot ulceration commonly associated with poorer quality of life (QoL). A positive SARC‐F test is predictive of sarcopenia. The objective of this study is to investigate whether SARC‐F positive status is associated with lower QoL among attendees of HRFC, which is currently unknown. Methods and results: In this cross‐sectional study ambulatory HRFC patients were recruited at metropolitan tertiary referral hospital over one year. Demographics, comorbidities, SARC‐F and EQ‐5D‐3L (EuroQol Group) outcomes were collected. Association between SARC‐F status and EQ‐5D visual analogue scale measurement, as well as individual EQ‐5D‐3L dimensions were investigated using, respectively, linear robust and ordinal logistic regression modelling. The clinic was attended by 122 new patients, 85 of whom (69%) completed the questionnaires with no selection bias identified. 43/85 (51%) patients were SARC‐F positive as indicated by a score of 4 or greater. No significant differences between SARC‐F positive and negative patients were identified in age or diabetes status. SARC‐F positive patients had consistently lower EQ‐5D‐3L visual analogue scale measurement [mean 5.3 (SD 2.0); median 5 (IQR: 4, 6.5)] compared to SARC‐F negative patients [6.6 (SD 1.9); 7 (5.5, 7.5)], adjusted mean difference ‐1.2 (95%CI: ‐2.1, ‐0.4; p=0.007). SARC‐F positive patients demonstrated consistent and statistically significantly worse EQ‐5D‐3L scores on mobility, personal care and usual activities, but not on anxiety/depression and pain/discomfort components. Conclusions: Approximately half of HRFC patients are SARC‐F positive and exhibit significantly lower QoL as measured by EQ‐5D‐3L compared to SARC‐F negative patients.